Prevalence and contributing factors to recurrent binge eating and obesity among black adults with food insufficiency: findings from a cross-sectional study from a nationally-representative sample - Rachel W. Goode (BMC, 2021)
Plain English Summary Living in a food-insufficient household may increase risk for binge eating and obesity. Because we know very little about this relationship in Black Americans, we conducted a research study to examine the rates of food insufficiency, binge eating, and obesity in a sample of African Americans and Afro-Caribbeans. The prevalence of food insufficiency in the entire sample was 10.9%. In Afro-Caribbeans, individuals with food insufficiency were more likely to have obesity, than those who were food sufficient. We did not see this relationship in African Americans. Individuals with food insufficiency were more likely to report recurrent binge eating in the last 12 months, compared to those with food sufficiency. After adjusting for socio-demographic factors, however, food insufficiency was not significantly associated with recurrent binge eating.